Preparing Teaching Materials for Speaking Skills Based on The 2013 Curriculum at The Middle School "Al-Bashor" Lamongan - Mimi Jamilah; Jasril Jasril (Gunung Djati Conference Series, 2023)
It is widely known that Arabic has been considered the language of international communication. Even the United Nations, or UN for short, recognizes it as the world's second-largest and most populous language after English. However, despite the outstanding achievements of the Qur'anic language, it is miserable, the awareness to always communicate Arabic in Indonesia, especially in educational institutions and especially MTS Al-Bashor, is still very weak. The most dominant factor occurs because Arabic teaching materials at MTS Al-Bashor only use Student Worksheets (Student Worksheets), which are considered less motivating for students to develop speaking skills in Arabic. To overcome this problem, the authors designed Arabic teaching materials that are colored with various exercises to support children to be able to speak Arabic, designed using a scientific approach and skills according to the 2013 curriculum to improve speaking skills for 7th-grade students of MTS Al-Bashor Sidokumpul Lamongan. With this design, students can speak Arabic correctly, grammatically, fluently, fluently, and rich vocabulary. With this aim, the authors conducted this research with research and development methods (Research & Development) with a quantitative approach to producing products that teach materials and test product effectiveness. This study uses instruments, and there are tests and interviews. After the authors design teaching materials, conduct experiments, and analyze all data, the authors get a summary; 1) This teaching material product is a book whose text content and method are rated good 76%, which means this book is suitable for teaching and learning. 2) This teaching material is effective for improving speaking skills for students; it is based on the pretest and post-test results, which increased from an average of 69.28% to an average of 81.00% in the post-test. This is supported by the results of interviews that most of the students had good grades and improved.